Clinical chemistry, immunology, and laboratory quality control : a comprehensive review for board preparation, certification, and clinical practice - DasGupta, Amitava; Wahed, Amer (Amsterdam ; Boston : Elsevier, 2014)
All pathology residents must have a good command of clinical chemistry, toxicology, immunology, and laboratorystatistics to be successful pathologists, as well as to pass the American Board of Pathology examination. Clinicalchemistry, however, is a topic in which many senior medical students and pathology residents face challenges. Clinical Chemistry, Immunology and Laboratory Quality Control meets this challenge head on with a clear and easy-to-read presentation of core topics and detailed case studies that illustrate the application of clinical chemistry knowledge to everyday patterns
Includes bibliographical references and index
1 13
Keywords: Clinical chemistry; Clinical Chemistry Tests -- methods; Clinical chemistry; Immunologic Tests -- methods